A case report on angioedema induced by ramipril in a patient treated in a tertiary care hospital in north India - Sankalp; Tewari, Sachchidanand (International Journal of Basic & Clinical Pharmacology, 2023)
Angioedema is non-pitting edema, or swelling, of the area beneath the deep dermis, subcutaneous, and/or mucosal layers of tissue resulting from fluid buildup, and it can be fatal if the larynx and pharynx are implicated. Drug-induced angioedema, like other cutaneous drug reactions, is most frequently elicited by non-steroidal anti-inflammatory drugs and beta-lactam antibiotics, while reliable information obtained from epidemiologic research is lacking. The latest studies have revealed that angiotensin-converting enzyme inhibitors have an increasing role in the development of life-threatening angioedema. Because of its safety and efficacy, ramipril is a commonly prescribed ACEI. This case report describes the clinical manifestations, management, and outcome of ramipril-induced facial angioedema in a 70-year-old Indian man.